Tracking of Human Subjects with Infrared Imaging - Lee, Donghyub; Yeom, Seokwon (2018 Joint 10th International Conference on Soft Computing and Intelligent Systems (SCIS) and 19th International Symposium on Advanced Intelligent Systems (ISIS), 2018)
Human detection and tracking at night are important for smart surveillance. Infrared (IR) imaging can detect humans at night. In this paper, we address the tracking of moving human subjects with IR images. Multi-level segmentation is adopted for human detection. In multi-level segmentation, the region extracted at one level is input to the next level segmentation. The centroids of detected objects are tracked by Kalman filtering. In the experiment, three moving person groups are successfully tracked.